Plasminogen Activator Inhibitor-1 Suppresses Profibrotic Responses in Fibroblasts from Fibrotic Lungs - Marudamuthu, Amarnath S. (J Biol Chem, 2015)
Idiopathic pulmonary fibrosis (IPF) is a fatal lung disease characterized by progressive interstitial scarification. A hallmark morphological lesion is the accumulation of myofibroblasts or fibrotic lung fibroblasts (FL-fibroblasts) in areas called fibroblastic foci. We previously demonstrated that the expression of both urokinase-type plasminogen activator (uPA) and the uPA receptor are elevated in FL-fibroblasts from the lungs of patients with IPF. FL-fibroblasts isolated from human IPF lungs and from mice with bleomycin-induced pulmonary fibrosis showed an increased rate of proliferation compared with normal lung fibroblasts (NL-fibroblasts) derived from histologically “normal” lung. Basal expression of plasminogen activator inhibitor-1 (PAI-1) in human and murine FL-fibroblasts was reduced, whereas collagen-I and α-smooth muscle actin were markedly elevated. Conversely, alveolar type II epithelial cells surrounding the fibrotic foci in situ, as well as those isolated from IPF lungs, showed increased activation of caspase-3 and PAI-1 with a parallel reduction in uPA expression. Transduction of an adenovirus PAI-1 cDNA construct (Ad-PAI-1) suppressed expression of uPA and collagen-I and attenuated proliferation in FL-fibroblasts. On the contrary, inhibition of basal PAI-1 in NL-fibroblasts increased collagen-I and α-smooth muscle actin. Fibroblasts isolated from PAI-1-deficient mice without lung injury also showed increased collagen-I and uPA. These changes were associated with increased Akt/phosphatase and tensin homolog proliferation/survival signals in FL-fibroblasts, which were reversed by transduction with Ad-PAI-1. This study defines a new role of PAI-1 in the control of fibroblast activation and expansion and its role in the pathogenesis of fibrosing lung disease and, in particular, IPF.